2020
DOI: 10.1155/2020/4607197
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism by which TRAF6 Participates in the Immune Regulation of Autoimmune Diseases and Cancer

Abstract: Tumor necrosis factor (TNF) receptor-associated factor 6 (TRAF6), an E3 ubiquitin ligase, is a signal transduction molecule shared by the interleukin-1 receptor (IL-1R)/Toll-like receptor (TLR) family and the TNFR superfamily. TRAF6 has a unique TRAF domain and RING finger domain that mediate intracellular signaling events. In the immune system, TRAF6-mediated signaling has been shown to be critical for the development, homeostasis, and activation of a variety of immune cells, including B cells, T cells, dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 141 publications
0
16
0
Order By: Relevance
“…This pathway has been described to contribute to all stages of liver disease progression, from initial liver injury through inflammation and fibrosis to cirrhosis and hepatocellular carcinoma (HCC) (1315). Moreover, TRAF6 Mediated Induction of proinflammatory cytokines is a key driving force of proinflammatory and profibrogenic responses in NASH (16) and has been described as a possible contributor to progression to HCC (17). TLR4 signaling repertoire is involved in a variety of liver injury including that induced by NASH, which has been shown to play a key role during fibrogenesis in preclinical models of NAFLD (18), as wells as to enhance TGF-β signaling (19).…”
Section: Resultsmentioning
confidence: 99%
“…This pathway has been described to contribute to all stages of liver disease progression, from initial liver injury through inflammation and fibrosis to cirrhosis and hepatocellular carcinoma (HCC) (1315). Moreover, TRAF6 Mediated Induction of proinflammatory cytokines is a key driving force of proinflammatory and profibrogenic responses in NASH (16) and has been described as a possible contributor to progression to HCC (17). TLR4 signaling repertoire is involved in a variety of liver injury including that induced by NASH, which has been shown to play a key role during fibrogenesis in preclinical models of NAFLD (18), as wells as to enhance TGF-β signaling (19).…”
Section: Resultsmentioning
confidence: 99%
“…Tumor necrosis factor receptor-associated factor 6 (TRAF6) is a signaling protein of the interleukin-1 receptor (IL-1R)/Toll-like receptor (TLR) family and the TNFR superfamily. TRAF6 inhibition has previously been demonstrated to decrease cytokines, attenuate immunological responses, and promote M.tb survival (32). It was observed that M.tb infection resulted in increased expression of TRAF6 in TCRb−/− as well as in wild-type mice but transfer of CD4+ T cells further significantly increased the mRNA expression of TRAF6 in TCRb −/− mice while no change was found in wild-type mice.…”
Section: Discussionmentioning
confidence: 98%
“…Tumor necrosis factor receptor-associated factor 6 (TRAF6), an E3 ubiquitin ligase, is a signaling protein of the interleukin-1 receptor (IL-1R)/Toll-like receptor (TLR) family and the TNFR superfamily (32). In this study, we also examined the mRNA expression of TRAF-6 in lung macrophages.…”
Section: Mrna Expression Of Inflammation Associated Markers In Lung Macrophagesmentioning
confidence: 99%
“…The upregulation of autophagy leads to the resistance of cancer cells to various anticancer drugs [ 56 , 57 ]. Upon cellular stimuli including TLRs, IL-17R, and TNFR, TRAF6 regulates tumor cell proliferation, survival, apoptosis, and invasion through different signaling pathways [ 8 , 58 ]. As depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%